New exact traveling wave solutions for DS-I and DS-II equations - Yildirim, Ahmet; Paghaleh, Ameneh Samiei Samiei; Mirzazadeh, Mohammad; Moosaei, Hossein; Biswas, Anjan (Nonlinear Analysis: Modelling and Control, 2012)
In this present work, the simplest equation method is used to construct exact solutions of the DS-I and DS-II equations. The simplest equation method is a powerful solution method for obtaining exact solutions of nonlinear evolution equations. This method can be applied to nonintegrable equations as well as to integrable ones.